PENGEMBANGAN VIDEO PEMBELAJARAN IPA TEMA TEKNOLOGI KEHIDUPANKU DALAM MENUMBUHKAN MINAT BELAJAR DAN LITERASI DIGITAL SISWA - Koimah Koimah; Liska Berlian; Raden Amad Zaky EL Islami (PendIPA Journal of Science Education, 2026)
This research is motivated by the lack of use of learning media, especially audio-visual media that is more interesting, so that students have difficulty in understanding the material on the theme of my life Technology and the lack of digital literacy. The purpose of the study is to describe the level of validity of the Science Learning video on the theme of my life technology in fostering students' interest in learning and digital literacy and to describe the level of student response related to the Science learning video on the theme of my life Technology in fostering students' interest in learning and digital literacy. The method used is research and development (ADDIE). The research instruments used in this study are interviews, validation sheets and student response level instruments. In this development, it is limited only to development. The results of the study show the level of validity of the Science Learning video on the theme of my life technology in fostering students' interest in learning and digital literacy with a very valid category, amounting to 93.53% with details, from media expert validators of 92.5% with a very valid category, material expert validators of 90.41% with a very valid category science teacher expert validators of 95.83% with a very valid category and student response level of 91.9% with the strongly agree category. The learning interest indicator scored 94.5% with the very good category, and digital literacy scored 93.76% with the very good category.